The Influence Of Good Corporate Governance, Intellectual Capital, And Investment Opportunity Set On Company Value - Nopagia, Nopagia; Suripto, Suripto; Holiawati, Holiawati (Jurnal Ekonomi, 2024)
In facing various challenges that can threaten business value, an in-depth investigation is necessary. Market trust and company prospects are highly influenced by a company's high value. This research aims to explore how effective corporate management, intellectual resources, and investment opportunities impact company value. The data used in this study is sourced from the annual financial reports of companies listed on the Indonesia Stock Exchange, specifically those included in the LQ45 index. The research employs a quantitative approach, focusing on the associative relationship between the aforementioned variables. A purposive sampling method was used for sample selection, with specific criteria set in advance. A total of 22 companies were selected as the research sample, and data was observed over a 5-year period, resulting in 110 observational data points used for analysis. The Ordinary Least Squares (OLS) method was used in this study to test the proposed hypotheses. The results show that while the investment opportunity set and intellectual resources have a positive and significant effect on company value, good corporate management does not have a significant impact on company value. This indicates that in maintaining company value, the management of intellectual resources and investment opportunities may play a more significant role than good corporate governance. In the long term, company value can continue to grow, and stakeholders will take note of this development. Therefore, companies need to keep striving to maximize their performance by considering the internal and external conditions that affect their value.